The Degree of the Contribution of Self-exploration to Technological Well-being among the Electronic Extortion-victim Students in Karak Governorate - Khatatneh, Sami (Dirasat: Human and Social Sciences, 2023)
The current study aimed to identify the level of both self-exploration and technological wellness among a group of Mutah University students who are victims of electronic extortion and to investigate the degree of contribution to self-exploration in their technological wellness. The research included (64) male and female students (26) male and (38) female students. The descriptive and predictive approach was used. The results of the research concluded that the level of self-exploration and technological wellness came to a medium degree and that the dimensions of self-exploration predict technological wellness with an amount of (27%), and there are no differences between males and females in self-exploration and technological wellness. Focus by counselors on improving self-exploration and technological wellness among students who are victims of electronic extortion.